Investigating The Role Of Student Organizations In Fostering Civic Engagement And Leadership Skills In Pakistani Universities - Mamoona Anam , Dr. Shakeel Ahmed , Ar. Abdullah Saeed , Dr. Nailah Riaz , Muhammad Hamid Nawaz Khan , Dr. Muhammad Asghar , Kashif Lodhi (Migration Letters, 2024)
This study examines the impact of student organizations on promoting civic engagement and developing leadership abilities in Pakistani colleges through a mixed-methods methodology. The researchers gathered quantitative data by distributing structured questionnaires to a stratified random sample of students who were members of different student groups at several universities. The questionnaires aimed to assess the students’ levels of civic engagement and perceived growth of leadership skills. In addition, we collected qualitative data through extensive semi-structured interviews with student leaders, academic advisers, and university administrators. This allowed us to develop a more profound understanding of the ways in which student groups’ impact these outcomes. Statistical approaches were used to assess the quantitative data, while thematic analysis was used for the qualitative data to identify important patterns and correlations. The results indicate that involvement in student organizations has a substantial impact on students’ civic engagement and leadership abilities, with noticeable differences depending on the specific type of organization and demographic characteristics. The importance of student organizations in the overall growth of university students in Pakistan is emphasized by this thorough comprehension, emphasizing the necessity for institutional assistance to optimize their beneficial influence.